1998
DOI: 10.1074/jbc.273.22.13703
|View full text |Cite
|
Sign up to set email alerts
|

Transient Poly(ADP-ribosyl)ation of Nuclear Proteins and Role of Poly(ADP-ribose) Polymerase in the Early Stages of Apoptosis

Abstract: Apoptosis, or programmed cell death, plays important roles in development, homeostasis, and immunological competence.It is characterized by marked morphological changes such as membrane blebbing, chromatin condensation, nuclear breakdown, and the appearance of membrane-associated apoptotic bodies, as well as by internucleosomal DNA fragmentation. The enzyme poly(ADP-ribose) polymerase (PARP) 1 catalyzes the poly(ADP-ribosyl)ation of various nuclear proteins with NAD as substrate, and, because it is activated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
175
6
2

Year Published

1999
1999
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 258 publications
(193 citation statements)
references
References 55 publications
10
175
6
2
Order By: Relevance
“…To determine whether depletion of PARP by gene disruption similarly blocks reentry of cells into S phase, we studied immortalized ®broblasts that were derived from wild-type (control) and PARP knockout (PARP7/7) mice (Wang et al, 1995). These PARP7/7 cells were previously con®rmed to be devoid of detectable PARP and poly(ADP-ribose) by immunoblot analysis with the corresponding antibodies (Simbulan-Rosenthal et al, 1998b). Although the presence of a novel activity capable of synthesizing ADP-ribose polymers has been shown recently in PARP7/7 cells, this activity, which is induced by treatment with MNNG, is considerably less than that in wild-type cells and may not fully compensate for PARP depletion (Shieh et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine whether depletion of PARP by gene disruption similarly blocks reentry of cells into S phase, we studied immortalized ®broblasts that were derived from wild-type (control) and PARP knockout (PARP7/7) mice (Wang et al, 1995). These PARP7/7 cells were previously con®rmed to be devoid of detectable PARP and poly(ADP-ribose) by immunoblot analysis with the corresponding antibodies (Simbulan-Rosenthal et al, 1998b). Although the presence of a novel activity capable of synthesizing ADP-ribose polymers has been shown recently in PARP7/7 cells, this activity, which is induced by treatment with MNNG, is considerably less than that in wild-type cells and may not fully compensate for PARP depletion (Shieh et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…DNA histograms were derived at various times after release from aphidicolin block and the cell cycle phase distribution was quanti®ed and summarized in a ®gure showing per cent of wild-type (closed circles) and PARP7/7 (open circles) cells in S phase of the cell cycle PARP7/7 ®broblasts were stably transfected with pCD12, a plasmid encoding wild-type PARP, and grown in selective medium. A stable clone was selected for further study on the basis of its ability to express PARP protein as revealed by immunoblot analysis with antibodies to PARP as well as by PARP activity assays (Simbulan-Rosenthal et al, 1998b). These PARP7/ 7(+PARP) cells were synchronized by serum deprivation, released into the cell cycle by addition of serum, and analysed by¯ow cytometry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2a shows the measured volume distributions of PARP-1 molecules bound to the free ends in the three-way DNA junction model. On the basis of Jarque-Bera statistical analyses, the volumes show a normal distribution, with a mean volume of 255 6 63 nm 3 , which roughly corresponds to the size of a monomer. The theoretical molecular volume calculated from the protein's molecular weight is 213.7 nm 3 .…”
Section: Resultsmentioning
confidence: 99%
“…PARP-1 has been implicated in the DNA damage response as well as in cell growth, regulation, and apoptosis (2)(3)(4). The structure of the 113 kDa PARP-1 protein consists of three functional domains: the DNA binding domain, the central automodification domain, and the catalytic domain (5,6).…”
mentioning
confidence: 99%